2021
DOI: 10.3390/insects13010028
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Editing Silkworms (Bombyx mori) Genome by Using the CRISPR-Cas System

Abstract: CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR-associated) represents a powerful genome editing technology that revolutionized in a short period of time numerous natural sciences branches. Therefore, extraordinary progress was made in various fields, such as entomology or biotechnology. Bombyx mori is one of the most important insects, not only for the sericulture industry, but for numerous scientific areas. The silkworms play a key role as a model organism, but also as a biorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 164 publications
(163 reference statements)
0
12
0
Order By: Relevance
“…For this purpose, in the last decades, genetic engineering has made extraordinary progress. In this direction, various studies have reported the development of enhanced SF fibers ( Table 2 ) [ 91 , 92 , 93 ].…”
Section: Sf Key Propertiesmentioning
confidence: 99%
“…For this purpose, in the last decades, genetic engineering has made extraordinary progress. In this direction, various studies have reported the development of enhanced SF fibers ( Table 2 ) [ 91 , 92 , 93 ].…”
Section: Sf Key Propertiesmentioning
confidence: 99%
“…The silkworm Bombyx mori serves as the most prominent lepidopteran species model system for molecular genetic analysis in lepidopterans ( Xu and O’Brochta 2015 ; Baci et al 2021 ). It was the first lepidopteran species with a fully sequenced genome, it is the focus of several extensive genomic databases and related resources, and there are robust methods for genetic manipulations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important roles of B. mori in the scientific fields is that of a model organism and bioreactor. It represents a valuable model organism for various human diseases due to the fact that its genetic information is well documented [ 23 ]. In addition, the silkworm’s genome contains a meaningful percent of human ortholog genes, and there are various mutant strains described [ 21 ].…”
Section: Introductionmentioning
confidence: 99%